Analysis of the electromagnetic wave front created by coherent sources of radiation from two points of space - A. A. Dyatko; S. M. Kostromitski; P. N. Shumski; I. N. Davydenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The front of electromagnetic wave generated by coherent sources of radiation from two points of space is analyzed in the article. General expressions are obtained that allow to estimate the directions of the arrival of the wave at a point in the space where the observer is situated (the angle-system), depending on the parameters of the radiators system. It is shown that the obtained relations for some particular cases coincide with the expressions presented in known publications on the subject under consideration.